DESENVOLVIMENTO ECONÔMICO, PREFERÊNCIA PELA LIQUIDEZ E ACESSO BANCÁRIO: UM ESTUDO DE CASO DAS MESORREGIÕES DE MINAS GERAIS - Crocco, Marco (2009)
The aim of this paper is to study the bank access and the public liquidity preference in Minas Gerais. The theoretical approach will be post-keynesian, which suggests that in peripherical regions the liquidity preference would be higher, due to the uncertainty. This situation leads to fewer agencies, less information within the peripheral region and lower willingness in lending by the bank system. In this way, regions with higher liquidity preferences and lower bank access are supposed to show credit problems, what make their development more difficult.